Positive electrodes with coated disordered rock-salt-type materials
By applying coatings of oxides, phosphates and other materials on the surface of lithium-ferrate anode materials, the problems of insufficient capacity retention and shortened battery life during recycling of lithium-ion batteries are solved, and the circulation performance and life of the battery are significantly improved.
Patent Information
- Application Number
- JP2024509137
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-08-31
- Filing Date
- 2022-08-26
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-08-26
AI Technical Summary
The unstable lithium-ferrate structure leads to insufficient battery capacity retention during recycling of lithium-ion batteries, and there is a problem of shortening battery life caused by overvoltage.
A coating is applied to the surface of the lithium-ferrate type anode material, which may contain oxides, phosphates, phosphides or fluorides to stabilize the anode material.
Through the application of coating, the circulation performance and battery life of lithium-ion batteries are significantly improved, reducing battery capacity degradation and overvoltage damage.
Smart Images

Figure 0007656995000003 
Figure 0007656995000004 
Figure 0007656995000005
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of battery technology, and more particularly to the field of high energy materials for use in the positive electrodes of electrochemical cells. [Background technology]
[0002] Lithium metal oxides are high energy density materials that are often used in lithium ion batteries. One form or class of lithium metal oxide has a disordered rock salt structure, where M is a trivalent cation, Formula (1): xLi3NbO4·(1-x)LiMO2(1) Compositions represented by formula (1) have shown promise for use as positive electrodes in lithium-ion batteries. Disordered rock-salt compositions, such as those represented by formula (1), generally have random atomic arrangements of close-packed lithium ions and transition metal ions in a cubic crystal structure. These disordered rock-salt compositions can contain more lithium atoms per formula unit than traditional lithium-rich layered structures.
[0003] The disordered rock-salt structure is an attractive cathode material for next-generation lithium-ion batteries due to its high specific energy density. For example, one disordered rock-salt structure material has a theoretical gravimetric energy density of about 1120 Wh / kg. The disordered rock-salt material can also be formed using relatively low-cost raw materials such as manganese. Thus, the disordered rock-salt material can achieve a relatively high energy density with a relatively low material cost. To achieve a comparable energy density, other types of known cathode materials use higher-cost raw materials such as cobalt and / or nickel. Summary of the Invention [Problem to be solved by the invention]
[0004] One of the challenges in using disordered rock-salt materials in secondary batteries is poor capacity retention upon cycling. The poor capacity retention can be attributed to anionic redox instability and cycling at high voltages, which results in side reactions during charging. The side reactions can involve residual lithium salts, such as lithium hydroxide (LiOH) and lithium carbonate (Li2CO3), that can be present on the surface of lithium-rich materials and are detrimental to the electrochemical performance of the battery. Disordered rock-salt materials can also have residual lithium salts based on the pH value of the cathode material. The by-products of the side reactions can increase the cell resistance, and the large cell resistance can reduce the cycle life of the disordered rock-salt materials due to overvoltage. The true state of charge (SOC) and depth of discharge (DOD) ranges shrink with increasing cycle numbers, which leads to reduced cycle capacity. [Means for solving the problem]
[0005] Embodiments of the present subject matter described herein relate to improving the cycling performance of electrochemical cells having disordered rock-salt type positive electrodes. For example, embodiments described herein may increase the capacity retention of an electrochemical cell by stabilizing the disordered rock-salt type material. The disordered rock-salt type material is stabilized by applying a coating layer to a surface of the disordered rock-salt type material.
[0006] In one or more embodiments, a positive electrode is provided that includes a disordered rock-salt phase material and a coating layer disposed on the surface of the disordered rock-salt phase material. The coating layer may include one or more of an oxide, a phosphate, a phosphide, or a fluoride. Desirably, the layer includes a phosphate, a phosphide, or a combination thereof.
[0007] Optionally, the disordered rock salt phase material may have the chemical formula (i): Li x N y M z O b-a F a (i) It is represented by, where 1.0 < x < 1.65; 0 ≤ y < 0.55; 0.1 < z < 1; 0 ≤ a < 0.8; 1 ≤ b ≤ 3; N is one of Nb, Ti, Ta, Zr, W, Sb, or Mo; M is one of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Zr, Y, Mo, Ru, Rh, or Sb. Optionally, b = 2.
[0008] Optionally, the coating layer is present in an amount of 0.05% by mass or more and 10% by mass or less based on the total mass of the irregular rock salt phase material and the coating layer. Optionally, the coating layer is present in an amount of 5% by mass based on the total mass of the irregular rock salt phase material and the coating layer. Optionally, the coating layer is present in an amount of 2% by mass based on the total mass of the irregular rock salt phase material and the coating layer.
[0009] Optionally, the coating layer contains one or more of LiAlO2, Li3Al2(PO4)3 / AlPO4, Li3PO4, or Li2TiO3 / TiO2.
[0010] Optionally, the irregular rock salt phase material has an Fm-3m crystal structure.
[0011] In one or more embodiments, a method of forming a positive electrode is provided. The method includes synthesizing a disordered rock salt phase material and mixing the disordered rock salt phase material with one or more coating precursors to form a mixture. The precursors may be those that are desired to form lithium phosphate, lithium metal phosphate, lithium phosphide, lithium metal phosphide, or combinations thereof. The one or more coating precursors may include one or more of Al(CH3CO2)3, AlPO4, H3PO3, NH4H2PO4, or TiO2. The method may also include annealing the mixture to form a coated disordered rock salt powder having a coating layer disposed on the surface of the disordered rock salt phase material. Illustratively, the precursors may decompose during annealing to form phosphoric acid, phosphine, or a combination thereof, which may then react with surface species typically found on lithium metal, such as lithium carbonate, lithium oxide, and lithium hydroxide, to form lithium phosphate, lithium phosphide, or a combination thereof. Another example may be the use of phosphine gas, with or without additional liquid or solid precursors, to ultimately create the desired coating composition. When lithium phosphate and lithium phosphide are present, they may be present in the coating in any desired ratio, typically ranging from 0.01, 0.1, 0.5 to 100, 90, 5 or 2 lithium phosphate / lithium phosphide.
[0012] The coating layer may include one or more of LiAlO2, Li3Al2(PO4)3 / AlPO4, Li3PO4, Li3P, and Li2TiO3 / TiO2.
[0013] Optionally, the annealing step comprises heating the mixture at a temperature of at least 200° C. and at most 800° C. for a period of at least 0.5 hours and at most 24 hours. Optionally, the annealing step comprises heating the mixture under a flow of argon (Ar) gas.
[0014] Optionally, the method further includes a step of manufacturing a positive electrode active material by kneading the coated irregular rock salt powder together with one or more carbon precursors after the annealing step.
[0015] Optionally, the step of synthesizing the irregular rock salt phase material includes a step of kneading a suspension of a rock salt precursor in a solvent to form a precursor mixture, a step of drying the precursor mixture, and a step of annealing the dried precursor mixture to produce an irregular rock salt phase material. The rock salt precursor may include one or more of, for example, MnO, Mn2O3, Li2CO3, LiF, LiOH, Nb2O5, or NbF5.
[0016] In one or more embodiments, a secondary battery is provided that includes a negative electrode, a positive electrode, and an electrolyte. The positive electrode enables reversible conversion of lithium ions. The positive electrode includes an irregular rock salt phase material having a coating as described herein. The electrolyte includes an organic solvent and a lithium salt.
[0017] Optionally, the irregular rock salt phase material has an Fm-3m crystal structure.
[0018] Optionally, the irregular rock salt phase material has the chemical formula (i): Li x N y M z O b-a F a (i) represented by the formula, where 1.0 < x < 1.65; 0 ≦ y < 0.55; 0.1 < z < 1; 0 ≦ a < 0.8; 1 ≦ b ≦ 3; N is one of Nb, Ti, Ta, Zr, W, Sb, or Mo; M is one of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Zr, Y, Mo, Ru, Rh, or Sb. Optionally, b = 2.
[0019] The coating may include one or more of LiAlO2, Li3Al2(PO4)3 / AlPO4, Li3PO4, Li3P, and Li2TiO3 / TiO2. This layer may include lithium phosphate, lithium phosphide, or a combination thereof.
[0020] The coating layer may be present in an amount from about 0.05, 0.1, 0.2, 0.5 or 1 weight percent to 10, 7, 5 or 3 weight percent of the weight of the disordered rock salt phase material and coating layer. [Brief description of the drawings]
[0021]
Figure 1
Figure 2A
Figure 2B
Figure 3A
Figure 3B
Figure 4A
Figure 4B
Figure 5A
Figure 5B
Figure 6
Figure 7
[0022] The following definitions apply to the described aspects of one or more embodiments of the subject matter of the present invention. These definitions may also be detailed herein. Each term is further explained and illustrated throughout the description, drawings, and examples. Any interpretation of a term in this description should take into account the entire description, drawings, and examples presented herein.
[0023] Nouns include plural referents unless the context clearly indicates otherwise. Thus, for example, a reference to an object may include plural objects unless the context clearly indicates otherwise.
[0024] The term "active material" refers to the material of an electrode, particularly the positive electrode, that donates, liberates, or otherwise provides conductive species during the electrochemical reaction in an electrochemical cell.
[0025] The term "metal" refers to alkali metals, alkaline earth metals, transition metals, lanthanides, and actinides as those terms are understood by those of skill in the art or as defined herein. The term "alkali metal" refers to any of the chemical elements in Group 1 of the periodic table, including lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), and francium (Fr). The term "alkaline earth metal" refers to any of the chemical elements in Group 2 of the periodic table, including beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), and radium (Ra). The term "transition metal" includes scandium (Sc), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), yttrium (Y), zirconium (Zr), niobium (Nb), molybdenum (Mo), technetium (Tc), ruthenium (Ru), rhodium (Rh), palladium (Pd), silver (Ag), Refers to the chemical elements in groups 3 to 12 of the periodic table, including cadmium (Cd), hafnium (Hf), tantalum (Ta), tungsten (W), rhenium (Re), osmium (Os), iridium (Ir), platinum (Pt), gold (Au), mercury (Hg), rutherfordium (Rf), dubnium (Db), seaborgium (Sg), bohrium (Bh), hassium (Hs), and meitnerium (Mt). The term "post-transition metals" refers to aluminum (Al), gallium (Ga), germanium (Ge), indium (In), tin (Sn), antimony (Sb), thallium (Tl), lead (Pb), bismuth (Bi), and polonium (Po).
[0026] The ratio "C" refers to either the discharge current as a fraction or multiple of a "1C" current value that would substantially fully discharge a battery (in a substantially fully charged state) in one hour, or the charge current as a fraction or multiple of a "1C" current value that would substantially fully charge a battery (in a substantially fully discharged state) in one hour, depending on the context.
[0027] To the extent that particular battery characteristics may vary with temperature, such characteristics are specified at 30 degrees Celsius (° C.) unless the context clearly indicates otherwise.
[0028] The ranges presented herein are inclusive of their endpoints, so for example, the range 1 to 3 includes values 1 and 3, as well as intermediate values between these endpoints.
[0029] Embodiments of the present subject matter provide disordered rock salt compositions and methodologies (e.g., structures) for use in constructing a positive electrode of an electrochemical cell. An electrochemical cell utilizing the disordered rock salt-type materials disclosed herein may be a secondary (e.g., rechargeable) battery. The secondary battery may be a lithium-ion battery. The lithium-ion battery includes an electrolyte formulation in which a lithium salt is present in a concentration suitable to conduct lithium ions through the electrolyte formulation between the electrodes (e.g., the positive and negative electrodes) during discharge and recharge operations. For example, the discharge and recharge of a lithium-ion battery may be accomplished by the exchange of lithium ions into and out of the positive and negative electrodes. The exchange may be characterized by intercalation and deintercalation and / or conversion of lithium ions. For example, some lithium ions may be exchanged by intercalation and other lithium ions may be exchanged by conversion. According to at least one embodiment, the positive electrode includes a disordered rock salt-type material.
[0030] In the disordered rock salt composition, both lithium and transition metals occupy a cubic close-packed lattice of octahedral sites. The disordered rock salt phase may have an Fm-3m rock salt crystal structure. In an electrochemical reaction, lithium diffusion proceeds by lithium ions hopping from one octahedral site to another via intermediate tetrahedral sites. Lithium at the intermediate tetrahedral site is in an active state in lithium diffusion. The activated tetrahedral lithium ions share faces at four tetrahedral sites as follows: (i) the position previously occupied by the lithium ion itself; (ii) the vacancy into which the lithium ion moves; and (iii and iv) two positions that can be occupied by lithium, a transition metal, or a vacancy.
[0031] The disordered rock salt phase materials of the cathodes described herein can have various compositions. This disordered rock salt chemical composition generally includes lithium, a transition metal, and oxygen. One or more of the positions of the transition metal or oxygen may be doped with another element to improve electrochemical performance. In a non-limiting example, the oxygen position is doped with fluorine. The chemical formula of the disordered rock salt phase material for potential doping at the oxygen position is of formula (i): Li x N y M z O b-a F a (i) wherein 1.0 < x < 1.65; 0 ≦ y < 0.55; 0.1 < z < 1; 0 ≦ a < 0.8; 1 ≦ b ≦ 3; N is one of Ti, Ta, Zr, W, Nb, Sb, or Mo; M is one of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Zr, Y, Mo, Ru, Rh, or Sb. In certain embodiments, y > 0.01. In certain embodiments, b = 2. In a non-limiting example, x + y + z = b, and thus the atomic ratio of metal (e.g., Li, N, and M) to non-metal (e.g., O and F) is equal. It is recognized that defects and / or anion deficiencies may occur, which would cause the total to deviate. These compositions have shown excellent specific capacity or energy density, such as about 350 mAh / g at 55 °C and C / 40, and about 300 mAh / g at 30 °C and C / 15.
[0032] For a>0, the presence of fluorine dopants at oxygen sites in disordered rock salts may improve the electrochemical performance of lithium-ion batteries. Without being bound by any particular theory or mechanism of action, anionic replacement of oxygen with fluorine (formation of oxyfluorides) may improve cycling performance by providing greater resistance to hydrogen fluoride attack due to electrolyte decomposition at high voltages. Alternatively, the higher ionicity of the metal-fluoride bond over that of the metal-oxygen bond may further stabilize the structure, with less transition metal leaching from the cathode into the electrolyte. Several disordered rock salt material compositions are disclosed in U.S. Patent Application Serial No. 15 / 222,377 (now U.S. Patent No. 10,280,092), incorporated herein by reference in its entirety.
[0033] Optionally, the disordered rock salt composition may be devoid of niobium (Nb). Instead of or in addition to the oxygen sites, the N and / or M metal sites may be doped, if desired.
[0034] The positive electrode according to one or more embodiments has a coating layer on the surface of the disordered rock-salt phase material. The coating modifies the surface of the disordered rock-salt material to improve the cycling performance of the battery. For example, the coating may provide a more stable and / or more conductive surface of the disordered rock-salt material (compared to formulations in which the surface of the disordered rock-salt material does not have a coating), which may reduce side reactions between the lithium salt and other compounds in the electrolyte. The coating may also stabilize by reducing overpotential. As a result, the coating improves cycling stability (e.g., capacity retention) within a range of operating temperatures, including room temperature.
[0035] Coatings are formed on the surface of the disordered rock salt phase material using oxide and / or phosphate coating precursors. For example, the coating precursors may include one or more phosphorus-containing compounds (e.g., phosphates, phosphides, and phosphites), oxides, fluorides, silicates, nitrides, carbonates, nitrates, borates, sulfates, acetates, and the like. Specific examples of coating precursors include, but are not limited to, aluminum acetate ("AlAc") (Al(CH3CO2)3), aluminum phosphate (AlPO4), phosphorous acid (H3PO3), ammonium dihydrogen phosphate (NH4H2PO4), and titanium oxide (TiO2). For example, the coating layer may be formed by using only one of the listed coating precursors or a combination of the listed precursors. Additionally, a gas may be introduced during annealing that reacts with surface species on the lithium metal, such as phosphine (PH3), which reacts with one or more species present in or on the lithium metal, such as to form lithium phosphide. The gas may also result from the decomposition of a solid or liquid precursor, such as the decomposition of phosphorous acid. The precursor may react with lithium ions present on the surface of the disordered rock-salt type material to form a thin coating layer over the surface. The lithium ions may be present as a leftover from the synthesis of the underlying disordered rock-salt phase material. The particular type and amount of coating precursor used may be selected based on a variety of factors, such as the particular precursor used to synthesize the disordered rock-salt phase. For example, one coating precursor may be more compatible with a particular disordered rock-salt composition than another disordered rock-salt composition. Compatibility in this context refers to the ability of the coating precursor to form and maintain a coating layer on the surface of the disordered rock-salt phase. Other factors may include the reactivity of the coating precursor with the disordered rock-salt phase, the conductivity of the coating precursor, and the like. For example, the coating precursor may be selected such that the resulting coating layer stabilizes the disordered rock-salt phase (e.g., by reducing side reactions) without significantly increasing the resistance to ion and / or electron transport to and from the cathode.
[0036] The composition of the coating layer is based on the particular coating precursor used in the synthesis process. The composition of the coating layer may include or exhibit oxides, fluorides, phosphates, silicates, nitrides, carbonates, nitrates, borates, and / or sulfates. Non-limiting examples of the composition of the coating layer include lithium aluminate (LiAlO2), aluminum phosphate doped aluminum stabilized NASICON structural material (Li3Al2(PO4)3 / AlPO4), lithium phosphate (Li3PO4), and / or lithium titanate doped titanium oxide (Li2TiO3 / TiO2). For example, an AlPO4 precursor can be used to produce a coating including Li3Al2(PO4)3 / AlPO4. An Al(CH3CO2)3 precursor can produce a coating including LiAlO2. An NH4H2PO4 precursor can produce a coating including Li3PO4, and a TiO2 precursor can produce Li2TiO3 / TiO2 during the coating. If desired, multiple coating precursors can be utilized to result in a coating layer including multiple compounds. For example, the coating layer may include multiples of LiAlO2, Li3Al2(PO4)3 / AlPO4, Li3PO4, and Li2TiO3 / TiO2. The coating layer may have other compositions in other embodiments, such as when precursors other than Al(CH3CO2)3, NH4H2PO4, AlPO4, and TiO2 are used instead of or in addition to one or more of the listed precursors. Another desirable example is the use of phosphorous acid, which may decompose to form phosphoric acid and phosphines that may result in coatings including lithium phosphide, lithium metal phosphide, lithium metal phosphate, and lithium phosphate. The metals of the phosphides and phosphates may be any suitable metal, such as transition metals or aluminum, and may include those metals described herein, including metals useful for producing disordered rock salts.
[0037] The amount of coating material relative to the disordered rock salt phase may also affect the cycling performance of the battery. In one or more embodiments, the coating layer is present between 0.05% and 10% by weight (e.g., 0.05% or more and 10% or less by weight) based on the total weight of the disordered rock salt phase material and the coating layer. For example, the coating content may be 0.05%, 0.1%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any non-zero intermediate amount (0-10%). In a first non-limiting example, the coating layer is present at 2% by weight. In a second non-limiting example, the coating layer is present at 5% by weight.
[0038] The coated disordered rock-salt type material can be used as a positive electrode active material in a battery. For example, the coated disordered rock-salt can be formed as a composite positive electrode film on a metal current collector. The coated disordered rock-salt type positive electrode generally improves initial coulombic efficiency (CE) and cycling capacity retention without substantially decreasing initial capacity as compared to a control cell having an uncoated disordered rock-salt type material as described herein. The favorable initial CE and capacity retention results indicate that the coating helps protect the disordered rock-salt phase from side reactions with compounds in the electrolyte during charging.
[0039] FIG 1 is a flow diagram 100 of a method for forming a positive electrode according to an embodiment. The method can be performed using laboratory and / or industrial equipment. More specifically, the method is used to produce a positive electrode active material having a coated disordered rock salt crystal structure. The method may include more, fewer, and / or different steps than those shown in FIG 1.
[0040] At 102, a disordered rock-salt phase material is synthesized. The disordered rock-salt phase material may be synthesized by solid-state chemical synthesis. For example, a suspension of rock-salt precursors may be prepared by mixing rock-salt precursors in a solvent. The rock-salt precursors may include metal compounds such as manganese oxide (Mn2O3), lithium carbonate (Li2CO3), lithium fluoride (LiF), lithium hydroxide (LiOH), niobium pentoxide (Nb2O5), and / or niobium fluoride (NbF5). The solvent may include deionized water. The precursors may be added in specific stoichiometric amounts according to the desired composition of the disordered rock-salt phase material. The suspension is then milled to form a precursor mixture. Milling may be performed using a planetary ball mill to reduce particle size and homogenize the mixture. Milling may be performed using other equipment in other embodiments.
[0041] After kneading, the precursor mixture is dried and then annealed. For example, the precursor mixture may be dried at 100° C. for 12 hours under air flow. The annealing process may include heating the dried mixture at a temperature between 750° C. and 900° C. for between 6 and 24 hours. The annealing process produces the disordered rock salt phase. For example, the heat causes the precursors to react and form a single phase. The conditions of the annealing step are selected to provide the desired crystal structure during calcination. For example, the conditions are selected so that the resulting disordered rock salt phase material has an Fm-3m crystal structure. Annealing at a temperature outside the specified range and / or for a time period outside the specified range may have undesirable effects on the crystal structure formed. If necessary, the annealing process may be performed under a gas flow such as argon (Ar). Alternatively, the annealing environment may be nitrogen gas (N2) or air instead of Ar.
[0042] The synthesized disordered rock salt phase material has the following chemical formula (i): Li x N y M z O b-a F a (i) may have the formula wherein 1.0 < x < 1.65; 0 ≦ y < 0.55; 0.1 < z < 1; 0 ≦ a < 0.8; 1 ≦ b ≦ 3; N is one of Ti, Ta, Zr, W, Nb, Sb, or Mo; M is one of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Zr, Y, Mo, Ru, Rh, or Sb. In certain embodiments, y > 0.01.
[0043] Next, at 104, the disordered rock salt phase material is mixed with one or more coating precursors to form a mixture. In non-limiting examples, the one or more coating precursors include Al(CH3CO2)3, AlPO4, NH4H2PO4, and / or TiO2. The coating precursors may be added to the mixture in specific amounts based on the desired composition and properties (e.g., thickness) of the coating layer to be formed.
[0044] At 106, the mixture of disordered rock-salt phase material and coating precursor is annealed to form a coated disordered rock-salt powder having a coating layer disposed on the surface of the disordered rock-salt phase material. The annealing step (e.g., post-annealing) may include heating the mixture at a temperature between 200° C. and 800° C. for a period between 0.5 hours and 24 hours. A narrower range of conditions includes heating the mixture at a temperature between 300° C. and 600° C. for a period between 10 hours and 14 hours. In one non-limiting example, the mixture may be heated at 300° C. for 12 hours. In another non-limiting example, the mixture may be heated at 600° C. for 12 hours. The heating may cause the coating precursor to react with the surface of the disordered rock-salt phase material. For example, the coating precursor may react with lithium ions present from residual lithium hydroxide, residual lithium carbonate, or within the disordered rock-salt phase itself to form a thin layer of coating material over the surface of the disordered rock-salt phase. Even if only limited reaction occurs, the annealing process may physically deposit a layer of coating precursor on the surface of the disordered rock salt phase. The annealing may be performed under a flow of Ar gas or another gas flow such as N2 or air. The surface coating layer may have a phosphate, oxide, and / or fluoride composition. For example, the composition of the coating layer may include oxides such as LiAlO2 or Li2TiO3 / TiO2, or phosphates such as Li3Al2(PO4)3 / AlPO4 or Li3PO4, based on the coating precursor or precursors utilized in the mixture.
[0045] In an embodiment, after the annealing step, the coated irregular rock salt powder is mixed with a carbon precursor to produce a positive electrode active material. The carbon precursor may include acetylene black, carbon black, carbon fiber, graphite, carbon nanotubes, KJ600, and the like. In an embodiment, the carbon precursor and the coated irregular rock salt powder are mixed in a ratio in which the irregular rock salt powder is in the majority. For example, the ratio of the coated irregular rock salt powder to the carbon precursor may be 60:40, 70:30, 80:20, 90:10, or greater. In an embodiment, the ratio of the coated irregular rock salt powder to the carbon precursor is greater than 90:10, such as 95:5, 96:4, or 97:3. In a non-limiting example used in experimental testing, the ratio is 96:4.
[0046] The active material may then be formed into a composite positive electrode film. For example, the active material powder (including the coated irregular rock salt powder with the carbon precursor) may be mixed with one or more solvents to form a slurry. Non-limiting examples of the one or more solvents include poly(vinylidene fluoride) ("PVDF") and 1-methyl-2-pyrrolidinone ("NMP"). The resulting slurry is deposited onto a metal current collector. The metal current collector may be stainless steel. The slurry on the metal current collector is then dried to form a composite positive electrode film.
[0047] The composite positive electrode film produced by the above-described method has a coated disordered rock salt crystal structure (e.g., Fm-3m structure). The composite positive electrode film can be utilized as a positive electrode in a secondary battery, such as a lithium ion battery. The battery includes a positive electrode and a negative electrode separated by a polymer separator. The battery includes an electrolyte that enables the transport of lithium ions and electrons between the positive electrode and the negative electrode. The positive electrode active materials described herein can be used with negative electrodes and electrolytes of various types and compositions.
[0048] In a non-limiting example, a secondary battery is formed with the composite cathode material as the cathode, an anode, a separator, and an electrolyte. The battery may be formed in a high purity argon filled glove box (M-Braum, O2 and humidity content <0.1 ppm). Examples of suitable anode materials include lithium, graphite ("Li x Examples of the negative electrode materials include conventional negative electrode materials used in lithium-ion batteries, such as ZnO, CrO, and other carbon, silicate, or oxide-based negative electrode materials, as well as composite alloys combining multiple negative electrode materials. In a non-limiting example, the negative electrode is a lithium negative electrode, such that lithium comprises at least 50% by weight of the total weight of the negative electrode active material. Optionally, the lithium content can be greater than 75% by weight, such as greater than 90% by weight. For example, the negative electrode active material can be at least 95% by weight or more lithium. In an alternative embodiment, the secondary battery may not include a negative electrode, and thus the battery is completely free of a lithium or graphite negative electrode. In this alternative embodiment, the positive electrode can provide lithium ions for the battery function.
[0049] The electrolyte may include at least one organic solvent and at least one lithium salt. The organic solvent may include one or more carbonate esters, such as ethylene carbonate ("EC"), ethyl methyl carbonate ("EMC"), diethyl carbonate ("DEC"), fluoroethylene carbonate ("FEC"), trifluoropropylene carbonate ("TFPC"), propylene carbonate ("PC"). The lithium salt may include lithium hexafluorophosphate ("LiPF6"), lithium bis(fluorosulfonyl)imide ("LiFSI"), lithium difluoro(oxalato)borate ("LiDFOB") (LiBF2(C2O4)), and the like. The electrolyte may be in a liquid, solid, gel, or other non-solid phase. In one example, the electrolyte is a liquid electrolyte. In another example, the electrolyte is a solid electrolyte. The separator may be a polymer, such as polypropylene.
[0050] The electrolyte, in a non-limiting example composition, includes LiPF6 in a mixture with EC and EMC solvent additives. The battery is then sealed and cycled. The battery may be cycled between 1.5V and 4.6V at 30°C. EXAMPLES
[0051] experiment To test the performance of the coated disordered rock-salt type material as a positive active material in secondary batteries, several test cells were fabricated, cycled, and then analyzed. The compositions and processes described in these experiments are non-limiting examples. The test cells were formed according to the methods described above, varying only certain properties. For example, stoichiometric amounts of rock-salt precursors (Mn2O3, Li2CO3, Nb2O5, and other dopants in oxide or fluoride form) were mixed in deionized water to produce a suspension, which was ball-milled in a planetary ball mill to reduce particle size and simultaneously prepare a homogenous mixture of all precursors. The mixture was dried at 100°C under air flow for 12 hours, and then annealed at 750-900°C under argon flow for 6-24 hours to obtain the disordered rock-salt phase.
[0052] The disordered rock salt phase material was then mixed with a specific amount of coating precursor, e.g., (Al(CH3CO2)3, AlPO4, NH4H2PO4, and TiO2, and then post-annealed under argon flow at either 300°C for 12 hours or 600°C for 12 hours, depending on the test cell, to form a coated disordered rock salt powder. The coated disordered rock salt powder was then kneaded with a carbon precursor in a ratio of 96:4 coated disordered rock salt powder to carbon to produce the active material for cathode casting. The active materials used in the test cells varied only in the type of coating precursor used, the amount of coating precursor (e.g., either 2% or 5% by weight based on the total active material weight), and the annealing temperature (e.g., 300°C or 600°C).
[0053] The batteries were formed in a high-purity argon-filled glove box (M-Braum, O2 and humidity content <0.1 ppm). The positive electrodes were prepared by mixing the active materials (e.g., coated irregular rock salt powder and carbon precursor) with the solvents poly(vinylidene fluoride) (Sigma Aldrich) and 1-methyl-2-pyrrolidinone (Sigma Aldrich). The resulting slurry was deposited on a stainless steel current collector and dried to form a composite positive electrode film. For the negative electrodes, thin Li foils were cut to the required size. Each battery comprised a composite positive electrode film, a polypropylene separator, and a lithium foil negative electrode. An electrolyte containing LiPF6 in a mixture of EC and EMC was used. The batteries were sealed and cycled from 1.5 to 4.6 V at 30 °C.
[0054] Two control test cells and 16 candidate test cells were fabricated. The control test cells did not have any coating material on the disordered rock salt type material. Each of the 16 test cells was provided with a coating layer based on either Al(CH3CO2)3, AlPO4, NH4H2PO4, or TiO2 such that four test cells had the (Al(CH3CO2)3 precursor, another four had the AlPO4 precursor, another four had the NH4H2PO4 precursor, and the final group of four had the TiO2 precursor. Half of the 16 test cells were provided with an amount of coating precursor to produce a coating layer that represented 2 wt. % of the total mass of the disordered rock salt phase material and coating precursor. The remaining test cells had a higher amount of coating precursor such that the coating layer comprised 5% by weight of the positive electrode active material. Finally, the post-annealing conditions were varied by heating the test cells at two different temperatures for the same amount of time. For example, half of the test cells were annealed at 300°C and the other half were annealed at 600°C. The test cells are identified and characterized in Tables 1 and 2 below. All of the test cells had disordered rock salt positive electrode material and a lithium negative electrode and were cycled from 1.5 to 4.6 V at 30°C with a 0.1 C charge (0.05 C CV) / 0.1 V discharge.
[0055] Table 1 shows cycling results of test cells having a coated random rock-salt cathode according to an embodiment compared to a control test cell, where all test cells in Table 1 were post-annealed at 300° C. for 12 hours. Table 2 shows cycling results of test cells having a coated random rock-salt cathode according to an embodiment compared to a control test cell, where all test cells in Table 2 were post-annealed at 600° C. for 12 hours. The tables show experimental results including first cycle capacity ("Cy1 Discharge Capacity") and first cycle coulombic efficiency ("Cy1 CE"). The first cycle capacity data is in units of mAh / g and the coulombic efficiency data is in percent (%).
[0056] [Table 1]
[0057] [Table 2]
[0058] The data from Tables 1 and 2 are graphed in Figures 2A and 2B. Figure 2A is a graph 200 plotting the initial (first cycle) discharge capacity for the 18 test cells identified in Tables 1 and 2. In Figure 2, the data from Table 1 (300°C annealed) is shown in the left half 202 of the plot, and the data from Table 2 (600°C annealed) is shown in the right half 204 of the plot. Graph 200 shows that most of the candidate test cells had similar or only slightly reduced initial discharge capacity compared to the control test cells. Only the four candidate cells containing Al(Ac)3 as the coating precursor showed significantly reduced discharge capacity compared to the control cells.
[0059] FIG. 2B is a graph 250 plotting the coulombic efficiency (CE) for the 18 test cells identified in Tables 1 and 2. The data from Tables 1 and 2 has been split in half as shown in FIG. 2A. Graph 250 shows that nearly all of the candidate test cells had improved initial CE over the control cell, except for a few compositions containing Al(CH3CO2)3. The cycling performance of these 18 test cells was tested, and the results are shown in FIGS. 3A, 3B, 4A, 4B, 5A, and 5B.
[0060] FIG. 3A is a graph 300 plotting discharge capacity versus cycle number for candidate test cells and control cells shown in Table 1 that were post-annealed at 300° C. FIG. 3B is a graph 350 plotting cycled capacity retention versus cycle number for candidate test cells and control cells shown in Table 1 and FIG. 3A. FIG. 4A is a graph 400 plotting discharge capacity versus cycle number for candidate test cells and control cells shown in Table 2 that were post-annealed at 600° C. FIG. 4B is a graph 450 plotting cycled capacity retention versus cycle number for candidate test cells and control cells shown in Table 2 and FIG. 4A.
[0061] 3A, 3B, 4A, and 4B show that all of the candidate test cells with the coated disordered rock salt cathode material provided improved cycling performance over the control test cells. The candidate test cells with the phosphate precursors AlPO4 and NH4H2PO4 were generally observed to perform better than the oxide coating precursors. The candidate test cells with the 5 wt. % coating were generally observed to have better cycling capacity retention than the 2 wt. % one under both post-annealing conditions, as shown in FIGS. 3B and 4B.
[0062] FIG. 5A is a graph 500 plotting CE versus cycle number for the candidate test cells and control cells shown in Table 1 that were post-annealed at 300° C. FIG. 5B is a graph 550 plotting cell resistance increase versus cycle number for the candidate test cells and control cells shown in Table 1 and FIG. 5A. The resistance increase is shown as a ratio of the resistance at a given cycle number to the resistance at the first or initial cycle ("Cyx / Cy1"). The trends plotted for CE cycling in FIG. 5A and cell resistance increase in FIG. 5B match well with the trends of cycled capacity retention shown in FIG. 2B. That is, the candidate test cells showed improved cycling performance over the control test cells with respect to limiting CE and cell resistance increase. The CE and cell resistance increase with cycle for the candidate cells post-annealed at 600° C. are not plotted because the results are similar to the trends shown in FIGS. 5A and 5B.
[0063] These experimental results show that the candidate test cells with the coated disordered rock-salt cathode material according to embodiments described herein exhibited better cycling performance than the control cells that did not have a coating on the disordered rock-salt cathode material. For example, the coating is believed to stabilize the surface of the disordered rock-salt, which results in better cycling performance. The fact that the candidate cells exhibit greater initial and cycled CE than the control cells when similar cycled capacities are obtained is an indication that fewer side reactions occurred between the disordered rock-salt phase material and the electrolyte during charging. Candidate test cells other than the cell with (Al(CH3CO2)3 were observed to have slightly less initial reversible capacity than the control, but this difference was small and was overshadowed by the gain in cycling performance. All coating precursors were shown to perform better than the control cell during cycling, however, the phosphate precursors AlPO4 and NH4H2PO4 generally performed slightly better than the oxide precursors and are therefore preferred. The TiO2 precursor generally performed better than the (Al(CH3CO2)3 precursor and therefore TiO2 is preferred over (Al(CH3CO2)3.
[0064] Another experiment using the same composition but different batches of random rock salt was coated in the same manner as described above for both the control and the coated random rock salt formed using phosphorous acid (H3PO3) precursor. The amount of phosphorous acid was 1% and 3% by weight of the random rock salt and phosphorous acid. Similarly, the phosphorous acid coated random rock salt at the same concentration was repeated with ammonium dihydrogen phosphate (ADP) using the same random rock salt and process. The phosphorous acid coated random rock salt was examined by scanning electron microscopy and energy dispersive X-ray analysis, which showed a relatively uniform phosphorus distribution. The cycling performance of the uncoated half-cell (control) and the phosphorous acid coated random rock salt type positive electrode and lithium metal negative electrode is shown in Figure 6. It is readily apparent that these coated random rock salt type positive electrode cells have substantially improved cycle life without sacrificing significant initial capacity. The ADP coated random rock salt half-cell improves cycling performance, but not to the same extent as the phosphorous acid coated random rock salt half-cell. It is believed, without being limited thereto, that phosphorous acid decomposes to form phosphoric acid and phosphine, which react to form lithium phosphate (Li3PO4) and lithium phosphide (Li3P), which may be the primary cause of the improved performance, i.e., it is believed, without being limited thereto in any way, that the presence of phosphine may be more beneficial for coating disordered rock salt cathode batteries.
[0065] A full cell of phosphorous-coated random rock salt is fabricated, which shows improved cycling performance compared to the half-cells, as shown in Figure 7, and achieves approximately twice the life of a cell with an uncoated random rock salt cathode (control).
[0066] As used herein, value modifiers such as "about," "substantially," and "approximately" preceding a numerical value indicate that the value may represent other values within a specified threshold range higher and / or lower than the stated value, such as values within 5%, 10%, or 15% of the stated value.
[0067] It should be understood that the foregoing description is intended to be illustrative, and not limiting. For example, the above-described embodiments (and / or aspects thereof) can be used in combination with each other. In addition, many modifications can be made to adapt a particular situation or material to the teachings of the various embodiments of the present disclosure without departing from their scope. While the dimensions and types of materials described herein are intended to define the parameters of the various embodiments of the present disclosure, the embodiments are in no way limiting, but are exemplary embodiments. Many other embodiments will be apparent to those skilled in the art upon review of the foregoing description. Thus, the scope of the various embodiments of the present disclosure should be determined by reference to the appended claims, along with the full scope of equivalents to which such claims are subject. In the appended claims and detailed description, the terms "including" and "in" are used as the plain English equivalents of the respective terms "including" and "in". Furthermore, the terms "first", "second" and "third", etc. are used merely as labels and are not intended to impose numerical requirements on their objects. Moreover, the following claim limitations are not recited in means-plus-function form and are not intended to be construed under 35 U.S.C. §112(f) unless such claim limitations expressly use the phrase "means for" followed by a statement of a function lacking structure.
[0068] The description set forth herein uses examples to disclose various embodiments of the disclosure, including the best mode, and to enable those skilled in the art to practice various embodiments of the disclosure, including making and using any devices or systems, and performing any incorporated methods. The patentable scope of the various embodiments of the disclosure is defined by the claims, and may include other examples that occur to those skilled in the art. Such other examples are intended to be within the scope of the claims if the examples have structural elements that do not differ from the literal language of the claims, or if the examples include equivalent structural elements that differ insignificantly from the literal language of the claims. Hereinafter, preferred embodiments of the present invention will be described item by item. Embodiment 1 An irregular rock salt phase material, and A coating layer disposed on the surface of the irregular rock salt phase material, the coating layer containing one or more of oxides, phosphates, phosphides, and fluorides. A positive electrode comprising the above. Embodiment 2 The irregular rock salt phase material has the chemical formula (i): Li x N y M z O b-a F a (i) wherein 1.0 < x < 1.65; 0 ≦ y < 0.55; 0.1 < z < 1; 0 ≦ a < 0.8; 1 ≦ b ≦ 3; N is one of Nb, Ti, Ta, Zr, W, Sb, or Mo; M is one of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Zr, Y, Mo, Ru, Rh, or Sb. The positive electrode according to Embodiment 1. Embodiment 3 b = 2. The positive electrode according to Embodiment 2. Embodiment 4 The coating layer is present in an amount of 0.05% by mass or more and 10% by mass or less based on the total mass of the irregular rock salt phase material and the coating layer. The positive electrode according to any one of Embodiments 1 to 3. Embodiment 5 The coating layer is present in an amount of 1 to 5% by mass based on the total mass of the irregular rock salt phase material and the coating layer. The positive electrode according to Embodiment 4. Embodiment 6 The coating layer is present in an amount of 2 to 4% by mass based on the total mass of the irregular rock salt phase material and the coating layer. The positive electrode according to Embodiment 4. Embodiment 7 The coating layer contains LiAlO 2 , Li 3 Al 2 (PO 4 ) 3 , AlPO 4 , Li 3 PO 4 , Li 3 P and Li 2 TiO 3 , TiO 2 One or more of the above. The positive electrode according to Embodiment 1. Embodiment 8 The coating layer contains Li 3 PO 4 and Li 3 P. The positive electrode according to Embodiment 7. Embodiment 9 The irregular rock salt phase material has an Fm-3m crystal structure. The positive electrode according to any one of Embodiments 1 to 8. Embodiment 10 In a method for forming a positive electrode, A step of mixing an irregular rock salt phase material with one or more coating precursors to form a mixture, wherein the one or more coating precursors include Al(CH 3 CO 2 )3 , a phosphate that decomposes during annealing to form lithium phosphate or lithium metal phosphate, lithium phosphide, lithium metal phosphide, and TiO 2 One or more of the above, and A step of annealing the mixture to form a coated irregular rock salt powder having a coating layer disposed on the surface of the irregular rock salt phase material. The method includes: EMBODIMENT 11 The phosphate decomposes to Li 3 PO 4 11. The method of embodiment 10, wherein the compound is formed. EMBODIMENT 12 12. The method of embodiment 10 or 11, wherein the phosphate decomposes to form phosphine. EMBODIMENT 13 13. The method of any one of embodiments 10 to 12, wherein phosphine is present during the annealing step. EMBODIMENT 14 14. The method of embodiment 13, wherein the phosphine reacts to form a phosphide. EMBODIMENT 15 The formed coating layer is LiAlO 2 , Li 3 Al 2 (PO 4 ) 3 , AlPO 4 , Li 3 PO 4 , Li 3 P, and Li 2 TiO 3 , TiO 2 15. The method of any one of embodiments 10 to 14, comprising one or more of the following: EMBODIMENT 16 16. The method of any one of claims 10 to 15, wherein the annealing step comprises heating the mixture at a temperature of 200°C to 800°C for a period of 0.5 hours to 24 hours. EMBODIMENT 17 11. The method of embodiment 10, wherein the annealing step comprises heating the mixture in an inert gas. EMBODIMENT 18 18. The method of embodiment 17, wherein the inert gas is flowing argon. EMBODIMENT 19 19. The method of any one of embodiments 10 to 18, further comprising compounding the coated irregular rock salt powder with one or more carbon precursors after the annealing step to produce a positive electrode active material. EMBODIMENT 20 20. The method of embodiment 19, wherein the carbon precursor comprises carbon nanotubes. EMBODIMENT 21 A secondary battery comprising the positive electrode according to any one of embodiments 1 to 9. EMBODIMENT 22 A secondary battery comprising a positive electrode formed by the method according to any one of embodiments 10 to 20. EMBODIMENT 23 2. The positive electrode of embodiment 1, wherein the phosphate is lithium phosphate, lithium metal phosphate, or a combination thereof, and the phosphide is lithium metal phosphide, lithium phosphide, or a combination thereof. EMBODIMENT 24 24. The positive electrode of embodiment 23, wherein the metal of the lithium metal phosphate and the lithium metal phosphide is a transition metal. EMBODIMENT 25 25. The positive electrode of embodiment 24, wherein the metal is a metal present in the disordered rock salt phase material.
Claims
1. Disordered rock-salt phase materials, and a coating layer disposed on a surface of the disordered rock salt phase material, the coating layer comprising one or more of titanium oxide, lithium metal phosphate, lithium phosphate, lithium metal oxide, and phosphide; Equipped with The disordered rock salt phase material has the chemical formula (i): Li x N y M z O ba F a (i) where 1.0<x<1.65; 0≦y<0.55; 0.1<z<1; 0≦a<0.8; 1≦b≦3; N is one of Nb, Ti, Ta, Zr, W, Sb, or Mo; and M is one of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Zr, Y, Mo, Ru, Rh, or Sb.
2. 2. The positive electrode of claim 1, wherein the coating layer is present in an amount of 0.05% by weight or more and 10% by weight or less, based on the total weight of the disordered rock salt phase material and the coating layer.
3. The coating layer is LiAlO 2 , Li 3 A 2 (P.O. 4 ) 3 , Li 3 P.O. 4 , Li 3 P and Li 2 TiO 3 , TiO 2 2. The positive electrode of claim 1 , comprising one or more of:
4. The coating layer is 3 P.O. 4 and Li 3 The positive electrode of claim 3 comprising P.
5. 1. A method of forming a positive electrode, comprising: Mixing the disordered rock salt phase material with one or more coating precursors to form a mixture, the one or more coating precursors being Al(CH 3 CO 2 ) 3 , phosphates, lithium phosphides, lithium metal phosphides and TiO which decompose during annealing to form lithium phosphate or lithium metal phosphate. 2 and annealing the mixture to form a coated irregular rock salt powder having a coating layer disposed on a surface of the irregular rock salt phase material; Including, The disordered rock salt phase material has the chemical formula (i): Li x N y M z O ba F a (i) where 1.0<x<1.65; 0≦y<0.55; 0.1<z<1; 0≦a<0.8; 1≦b≦3; N is one of Nb, Ti, Ta, Zr, W, Sb, or Mo; and M is one of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Zr, Y, Mo, Ru, Rh, or Sb.
6. The one or more coating precursors may be selected from the group consisting of phosphates, lithium phosphides, lithium metal phosphides, and TiO that decompose during annealing to form lithium phosphate or lithium metal phosphate. 2 and the phosphate is decomposed to Li 3 P.O. 4 The method of claim 5 , further comprising forming
7. The method of claim 5 , wherein phosphine is present during the annealing step.
8. The method of claim 7, wherein the phosphate decomposes to form phosphine.
9. The method of claim 7 , wherein the phosphine reacts to form a phosphide.
10. 8. The method of claim 7, wherein the annealing step comprises heating the mixture at a temperature of at least 200°C and at most 800°C for a period of at least 0.5 hours and at most 24 hours in an inert gas.
11. 11. The method of claim 5, further comprising the step of compounding the coated irregular rock salt powder with one or more carbon precursors after the annealing step to produce a positive electrode active material.
12. The method of claim 11 , wherein the carbon precursor comprises carbon nanotubes.
13. A secondary battery comprising the positive electrode according to any one of claims 1 to 4.
14. 5. The positive electrode of claim 1, wherein the phosphide is lithium metal phosphide, lithium phosphide, or a combination thereof, and the metal of the lithium metal phosphate and the lithium metal phosphide is a transition metal present in the disordered rock salt phase material.
Citation Information
Patent Citations
Oxides for high-energy cathode materials
JP2019523532A
Fluorine-substituted cation-disordered lithium metal oxide and its method of manufacture
JP2020515501A